2005
DOI: 10.1021/np0580356
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxylated Spirostanol Saponins from the Tubers of Dioscorea polygonoides

Abstract: Three new polyhydroxylated spirostanol saponins (1-3) were isolated from the tubers of Dioscorea polygonoides. The structures of these new compounds were determined on the basis of extensive spectroscopic analysis and the results of acid or enzymatic hydrolysis as (23S,24R,25S)-23,24-dihydroxyspirost-5-en-3beta-yl O-alpha-L-rhamnopyranosyl-(1-->2)-beta-D-glucopyranoside (1), (23S,25R)-12alpha,17alpha,23-trihydroxyspirost-5-en-3beta-yl O-alpha-L-rhamnopyranosyl-(1-->2)-beta-D-glucopyranoside (2), and (23S,25R)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The polyhydroxylated spirostanol saponins (41-43) did not exhibit cytotoxic activities against HSC-2 and HL-60 human promyelocytic leukemia cells (IC 50 > 200 lM), respectively [27].…”
Section: Dioscorea Polygonoidesmentioning
confidence: 91%
See 2 more Smart Citations
“…The polyhydroxylated spirostanol saponins (41-43) did not exhibit cytotoxic activities against HSC-2 and HL-60 human promyelocytic leukemia cells (IC 50 > 200 lM), respectively [27].…”
Section: Dioscorea Polygonoidesmentioning
confidence: 91%
“…hypoglauca [8][9][10][11][12][13], D. deltoidea var. orbiculata [14], D. futschauensis [15][16][17][18][19][20], D. nipponica [21], D. panthaica [22][23][24], D. parviflora [25], D. polygonoides [26,27], D. pseudojaponica [28], D. spongiosa [29], D. villosa [30], and D. zingiberensis [31] (Table 1). The structures of the aglycons of the isolated saponins belonged to three skeleton types: furostane, a pentacyclic ABCDE-ring system with a sixth open F ring (1-30); spirostane, a hexacyclic ABCDEF-ring system (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46); and pregnane, a tetracyclic ABCD-ring system (47-58) (Figs.…”
Section: Chemical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The R-methylene signal (δ 2.24) was correlated to a carbon signal at δ 34.2 (HMQC) and adjacent to the ester carbonyl at δ 173.5 (HMBC). The upfield section of the 13 C NMR spectrum showed a diversity of chemical shifts for methyl, methylene, and methine carbons; these data, together with DEPT NMR data, led to the construction of fragments corresponding to the normal, iso, and anteiso isomers of the acyl esters.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the upfield shift and coalescence of the H 2 -28 AB pair to a broad singlet at δ 3.61 confirmed that the enzymatic reaction had affected the target ester at C-28. The comparison of 13 C NMR spectra (acetone-d 6 ) showed a downfield shift of C-28 from δ 64.6 (3, acetone-d 6 ) to δ 70.9 (4), corresponding to the transformation from an ester to a primary alcohol. The NMR spectra indicated no other modifications in the candidaspongiolide core (4), confirming a successful enzymatic hydrolysis (Table 3).…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%